IDENTIFICATION OF JUNIOR HIGH SCHOOL STUDENTS’ ERROR TYPES IN UNDERSTANDING CONCEPT ABOUT RELATION AND FUNCTION - Aflich Yusnita Fitrianna; Rizky Rosjanuardi (IKIP Siliwangi and I-MES, 2021)
This study aims to identify types of errors made by students and their conceptions related to the concept of relations and functions. This research is a descriptive study with a qualitative approach conducted in eight grades at one of Madrasah Tsanawiyah in Kabupaten Bandung Barat. The research subjects were taken from 26 students who answered incorrectly on a given test. The research instrument was in the form of a diagnostic test based on basic competencies and indicators in the Relations and Function material. In-depth interviews were conducted with students who made mistakes in answering. Based on the data analysis, the mistakes made were: 1) conceptual error type 1, 2) conceptual error type 2, 3) procedural error, 4) technical error, and 5) error in understanding the problem. One of the causes of students' mistakes is the dissimilar concept between students’ and scientific conceptions.